2017
DOI: 10.1111/hsc.12519
|View full text |Cite
|
Sign up to set email alerts
|

Communicating risk in dementia care: Survey of health and social care professionals

Abstract: Supporting people to live at home in line with community care policies requires increasing attention to assessing, communicating and managing risks. There is a challenge in supporting client choices that include risk-taking while demonstrating professional accountability. Risk communication becomes increasingly important with the need to engage clients and families in meaningful shared decision-making. This presents particular challenges in dementia services. This survey of risk communication in dementia care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 98 publications
0
15
0
Order By: Relevance
“…Respecting autonomy and assessing health-risk in persons with dementia often appears to be an unsolvable dilemma that the health care professional needs to endure and remain in. Assessing and acting on risks in persons with dementia is challenging and professionals, family and the person with dementia may understand risk differently [ 34 , 42 ]. The value of autonomy is strong [ 43 , 44 ], and nurses in the present study emphasized that they aimed to respect the person’s preferences, even when contrary to what most people would want for themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respecting autonomy and assessing health-risk in persons with dementia often appears to be an unsolvable dilemma that the health care professional needs to endure and remain in. Assessing and acting on risks in persons with dementia is challenging and professionals, family and the person with dementia may understand risk differently [ 34 , 42 ]. The value of autonomy is strong [ 43 , 44 ], and nurses in the present study emphasized that they aimed to respect the person’s preferences, even when contrary to what most people would want for themselves.…”
Section: Discussionmentioning
confidence: 99%
“…They assessed needs within the context of what was possible to achieve without using forced treatment and care, i.e., living under very unsanitary conditions. Previous research has argued that nurses who support persons with dementia who live at home need to increase their attention to how to assess, communicate, and manage risk [ 34 , 42 ], and we add that they need to develop competence in how to balance these assessments with shared decision-making, self-determination, and the understanding of autonomy in persons with dementia. Based on the findings from our study, the nurses’ respect for the person’s preferences were enforced by working within their private homes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Stevenson et al, 2018;Stevenson & Taylor, 2017;Taylor et al, 2018) has shown that there are a number of risks related to health and well-being for a person with dementia who lives alone; for example, the risk of repeatedly getting lost outside of the home, of causing a fire, or of malnutrition. Based on the findings from this and previous research (Ulmanen & Szebehely, 2015), it is possible to question the policy of ageing in place for persons with dementia with complex care needs and comprehensive requirements for support in everyday life, and who also experience a number of risks in daily living.…”
Section: Discussionmentioning
confidence: 99%
“…When working in the homes of persons with dementia, home care staff are exposed to situations in which the person with dementia faces risks, for example risks in relation to activities such as cooking, managing money (Gilmour, Gibson, & Campbell, 2003), driving (Hunt, Brown, & Gilman, 2010), or getting lost while walking outside of the home (Robinson et al, 2007). The most common risks reported in the literature are risks to physical safety, such as falls (Muir, Gopaul, & Montero Odasso, 2012; and mismanagement of medication (Douglas, Letts, & Richardson, 2011;Taylor et al, 2018). However, psychosocial risks such as depression, loneliness or abuse from others are also mentioned (Taylor et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation